PERLINDUNGAN KONSUMEN DALAM JUAL BELI MELALUI TOKOPEDIA - Octavianto, Dwi Argo (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2025)
This research approach uses a descriptive analytical approach which is intended to provide an overview and analysis of the implementation of provisions in regulations which are based on applicable legal provisions. The research location is Tokopedia Semarang consumers. The type of data is primary data. The primary data in this thesis is a number of information or facts about legal protection for consumers in buying and selling on Tokopedia which were directly obtained from interviews with Tokopedia consumers. As a result of the research, information was obtained that legal protection for consumers in buying and selling on Tokopedia, namely legal protection for consumers, is regulated in Articles 4 and 5 of Law Number 8 of 1999 concerning Consumer Protection, Article 1243 of the Civil Code, Articles 1 (17), 46, 48 of Government Regulations Number 71 of 2019 concerning Implementation of Electronic Systems and Transactions. The legal consequences that arise regarding violations of consumer rights in online buying and selling by Tokopedia refer to Article 62 paragraph (1) of the Consumer Protection Law that business actors who violate consumer rights will be punished with a maximum imprisonment of 5 (five) years or a maximum fine. a lot of IDR 2 billion.